Efek Kecerdasan Intelektual, Emosional, Dan Spiritual Terhadap Akhlak Peserta Didik Di Sekolah Menengah Atas - Pasaleron, Roni; Rahman, Ikhwan; Fitriani, Fitriani; Irzain, Ismiati (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2023)
Intellectual, emotional and spiritual intelligence are important components in the moral development of high school students. Therefore, it is important for schools to develop these three intelligences in students. This research aims to examine the influence of intellectual, emotional and spiritual intelligence on the morals of high school students. This research uses quantitative methods with a survey approach. Samples were taken from 252 informant students through questionnaires using techniques simple random sampling andProportionate Stratified Random Sampling. All questionnaire results were then analyzed statistically usingSoftware SPSS Statistic 24.0 For Windows and SEM-AMOS analysis for simple regression. The results of the analysis show that intelligence has a significant effect on the morals of students with probability of 0.20 ≥ 0.05. Meanwhile intelligence has an emotional significant influence on students' morals with probability of 0.65 ≥ 0.05. Meanwhile intelligence has a significant influence on students' morals with probability of 0.80 ≥ 0.05. This means that the better the formation of intellectual intelligence, emotional, and spiritual the better the morals of secondary school students will be. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.